Tips on radiology for those challenging moments - Greenwood, G. (British dental journal, 2013)
Gillian Greenwood will be speaking on this subject on Thursday 25 April at the 2013 British Dental Conference & Exhibition held at ExCeL London. Register online: www.bda.org/conference We must be able to think 'outside the box' when taking radiographs for patients with challenging needs. The aim of this article and associated presentation at the 2013 British Dental Conference & Exhibition is to give an overview of methods to achieve radiographs for patients with special or additional care needs.